2018
DOI: 10.1021/acs.organomet.8b00313
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-Catalyzed Hydroamination and Multicomponent Coupling with a Simple Silica-Supported Catalyst

Abstract: Hydroamination and multicomponent coupling reactions catalyzed by homogeneous Ti(IV) complexes can produce valuable imines, amines, and other nitrogencontaining organic building blocks. Typically catalysts for this transformation are very sensitive to ancillary ligand design and often suffer from catalyst deactivation, necessitating use in a single reaction. Here, we have attempted to address these issues by moving toward a solid-supported Ti catalyst active for these reaction types. We present initial results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…This result is in line with Bergman’s finding that [Ti­(NAr)­Cp­(NHAr)­(py)] (Ar = 2,6-Me 2 C 6 H 4 ), which is structurally very similar to the surface complex 3s , efficiently catalyzes the hydroamination of diphenylacetylene, although the activity of 3s is significantly lower. On the other hand, the only reported heterogeneous Ti system operates under much harsher conditions, and thus this result is worth studying in more detail.…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This result is in line with Bergman’s finding that [Ti­(NAr)­Cp­(NHAr)­(py)] (Ar = 2,6-Me 2 C 6 H 4 ), which is structurally very similar to the surface complex 3s , efficiently catalyzes the hydroamination of diphenylacetylene, although the activity of 3s is significantly lower. On the other hand, the only reported heterogeneous Ti system operates under much harsher conditions, and thus this result is worth studying in more detail.…”
Section: Results and Discussionmentioning
confidence: 96%
“…In particular, cycloaddition with alkynes is a key elementary step in alkyne hydro­amination, , carboamination, and iminoamination, as well as in pyrrole synthesis via [2 + 2 + 1] coupling of alkynes with azo compounds and organic azides . Ti-catalyzed hydroamination of alkynes (Scheme ) has been extensively studied by many groups, especially by Odom, , who has also recently investigated the silica-supported systems . We have preliminarily tested the grafted catalysts 1s – 3s in the hydroamination of internal alkynes (which are known to be significantly more challenging substrates than the terminal alkynes) with p- toluidine (TolNH 2 ) at 5 mol % Ti loading in boiling toluene (110 °C).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Then, 2.5 equivalents of NaBH3CN were added (95%, 83 mg, 1.25 mmol) and stirred during 30 min. Then, a solution of p-toluenesulphonic acid (15 mol% in 2 mL of THF) was added dropwise, and stirred over 2-4 h more [6]. During this time, a small portion of bromocresol green was used as indicator, maintaining the solution in an orange-yellow colour (indicating acidic pH) [7].…”
Section: General Procedures For Reduction Of Imines To Aminesmentioning
confidence: 99%
“…23 The work of Basset, a pioneer of surface organometallic chemistry, has exhaustively reviewed the preparation and characterization of the highly reactive earlytransition-metal hydride species, supported on various oxides. 5,24 Among all investigated transition-metal systems, supported Ti species with adequately tuned coordination spheres were shown to play an important role in epoxidation, 25,26 hydroamination, 27 catalytic imido transfer, 28 polymerization, 29 and depolymerization processes. 11,12 Nevertheless, a detailed description of the surface Ti species remains still difficult to access.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among all investigated transition-metal systems, supported Ti species with adequately tuned coordination spheres were shown to play an important role in epoxidation, , hydroamination, catalytic imido transfer, polymerization, and depolymerization processes. , Nevertheless, a detailed description of the surface Ti species remains still difficult to access. Previously, it has been suggested that a proper choice of the dehydroxylation temperature of the support allows control of the distribution of surface hydroxyl groups and tuning their chemical reactivity .…”
Section: Introductionmentioning
confidence: 99%